1979
DOI: 10.1093/ajcp/71.2.177
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid (4-6-hour) Urine-culture System for Direct Identification and Direct Antimicrobial Susceptibility Testing

Abstract: This study evaluates a new direct rapid system for urine cultures, including detection and quantitation of positive specimens by Gram stain, direct identification by 4--6-hour incubation of sediment with reagent strips, and antibiotic susceptibility testing by direct (3--4-hour) disk-elution methods. Of 987 routine urine specimens, 121 had significant (less than or equal to 10(5) colony-forming units/ml) gram-negative bacilluria, of which 89% were detected by the Gram stain. Direct rapid identification was cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Most studies do not report an average cell concentration, but instead report the percentage of individuals having a positive and negative result. And microscopy results have been scored as positive if there has been greater than 0 (24,25,35), 1 or more (3,36,47), 2 or more (5,8,46), and 5 or more (20) bacterial cells per oil immersion field. These differing criteria can significantly impact the reported percentage of positive samples.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies do not report an average cell concentration, but instead report the percentage of individuals having a positive and negative result. And microscopy results have been scored as positive if there has been greater than 0 (24,25,35), 1 or more (3,36,47), 2 or more (5,8,46), and 5 or more (20) bacterial cells per oil immersion field. These differing criteria can significantly impact the reported percentage of positive samples.…”
Section: Discussionmentioning
confidence: 99%
“…screening of urines have included disappearance of glucose [ 14], tetrazolium reduction [15 ], nitrite detection [12], presence of catalase [12], bacterial adenosine 5'-triphosphate concentration [ 11 ], pyuria [19], Gram-stain [9,19], and automated photometric and nephelometric techniques [10,18]. Thrupp et al [18] and Jenkins et al [10] have reported satisfactory results with urine screening by light-scatter nephelometry and photometry, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This was a modification of previously described methods [7,9,19]. Ten microliters of unsedimented urine was placed with a calibrated platinum loop on a clean microscope slide and spread in a 25-30 mm circle.…”
Section: Screening Proceduresmentioning
confidence: 99%
See 2 more Smart Citations